2021
DOI: 10.1177/00469580211059965
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Knowledge, Attitude, and Practice Among Residents of Saudi Arabia Toward Hepatitis Viruses

Abstract: Background and aim: Data available in the Kingdom of Saudi Arabia (KSA) about public knowledge, attitude, and practice (KAP) toward viral hepatitis infection are scarce. Such information is essential for designing effective intervention strategies for the prevention and control of viral hepatitis. This study aimed to assess the knowledge, attitude, and practice among residents of KSA toward hepatitis viruses. Methods: A cross-sectional descriptive study was conducted among 549 participants in Saudi Arabia. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Most of the previous studies that were conducted in Saudi Arabia were limited to a certain population or geographical region. A prior study that was conducted in Saudi Arabia and published in 2021 concluded that 42% of participants showed low knowledge about viral hepatitis in general [20]. Another study that was conducted in the Riyadh region among dental students found that 37% of the students did not have adequate knowledge about HCV infection [21].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies that were conducted in Saudi Arabia were limited to a certain population or geographical region. A prior study that was conducted in Saudi Arabia and published in 2021 concluded that 42% of participants showed low knowledge about viral hepatitis in general [20]. Another study that was conducted in the Riyadh region among dental students found that 37% of the students did not have adequate knowledge about HCV infection [21].…”
Section: Discussionmentioning
confidence: 99%
“…This was the largest Australian study assessing knowledge and understanding of the effect, transmission, and treatment of HBV infection among chronically infected individuals. The findings highlighted the knowledge gaps and misconceptions held by the participants and the need to expand education and support initiatives 23,24 . The plausible reasons for differences in response could be the study tools used for the collection of data, study location, and the demographic variation of the study population.…”
Section: Discussionmentioning
confidence: 95%
“…Another study conducted in Rawalpindi, Pakistan showed poor knowledge, adequate attitude and poor practice towards hepatitis 22 . A study regarding knowledge, attitude and practice regarding viral hepatitis conducted in Saudi Arabia showed that most participants had not heard about hepatitis viruses and showed low level of knowledge on viral hepatitis (42%) 23 . Several other studies conducted in Iran, Brazil, Malaysia and India also showed inadequate levels of knowledge regarding viral hepatitis 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation